Immediate Effects of Yoga Based Relaxation Technique Yoga Nidra on Heart Rate Variability in Young and Healthy Volunteers - Chhetri, Praghosh; Shrestha, Lava; Rana, Binaya SJB; Banstola, Dinesh; Mahotra, Narayan Bahadur (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Cardiovascular autonomic functions are affected by the negative influences of stress which bring about alterations in heart rate variability (HRV). Yoga based relaxation techniques like Yoga Nidra have been found to relieve stress as shown by improved HRV. This study was conducted to assess the immediate effects of a yoga based guided relaxation technique, Yoga Nidra on HRV parameters in young and healthy volunteers.Methods: This was an interventional study conducted in the Department of Clinical Physiology, Institute of Medicine, Maharajgunj. Fifty two male medical students were divided into supine rest group (n=26) and Yoga Nidra group (n=26). HRV indices were recorded before and after supine rest and Yoga Nidra. Intra-group and inter-group comparisons of the HRV parameters were done before and after the interventions.Results: In comparison to the supine rest, Yoga Nidra produced significant increase in values of HF (1460.72 Vs 3272.99; p=0.03) and HFnu (50.32 Vs 62.68; p=0.004); and significant reduction in the values of LFnu (49.68 Vs 37.32; p=0.004) and LF:HF ratio (0.99 Vs 0.59; p=0.004), which suggested that the parasympathetic modulating response of Yoga Nidra was better than that of supine rest.Conclusion: Yoga Nidra, a yoga based relaxation technique brings better relaxation response than supine rest as indicated by the significantly improved HRV indices.